Products, practices and processes: exploring the innovation potential for low-carbon housing refurbishment among small and medium-sized enterprises (SMEs) in the UK construction industry - Killip, G (Elsevier, 2013)
Scenario-based studies agree that the technical potential for CO emissions reduction from the housing stock is large. This paper explores how a market might be developed for the refurbishment activities assumed in these scenarios, taking the existing market for repair, maintenance and improvement (RMI) as its starting point. Interviews with 16 small and medium-sized enterprises (SMEs) in the construction industry reveal the interdependence of products, practices and processes in housing renovation activities. Conservative practice as well as innovation can be understood as the outcome of multi-lateral influences on firms from other firms, clients, the material buildings and products in their working lives, and from regulations and regulators. Contractors' openness to innovation is contingent on an informal approach to risk assessment, taking account of cost, time efficiency, client demands, and installer confidence in the reliability of the resulting work. The implications of the research are discussed in relation to the need for new practices and processes on refurbishment projects, raising questions for future research on key questions of quality assurance, performance over time, the application of standards, and vocational training. © 2013 Elsevier Ltd. All rights reserved.